2021
DOI: 10.1161/jaha.121.021346
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Heart Transplantation Outcomes

Abstract: Background Patients with obesity and advanced heart failure face unique challenges on the path to heart transplantation. There are limited data on waitlist and transplantation outcomes in this population. We aimed to evaluate the impact of obesity on heart transplantation outcomes, and to investigate the effects of the new organ procurement and transplantation network allocation system in this population. Methods and Results This cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
2
8
0
Order By: Relevance
“…Another data registry study including 38.498 patients showed that underweight and obese patients had significantly higher risk for mortality 18 . In this context another recent registry study confirmed the results for obese patients 19 . However, previous evidence on influence of BMI on 1-year mortality is contradicting as other studies showed similar 1-year survival of obese patients compared to normal BMI patients 13 , 20 , 21 .…”
Section: Discussionsupporting
confidence: 75%
“…Another data registry study including 38.498 patients showed that underweight and obese patients had significantly higher risk for mortality 18 . In this context another recent registry study confirmed the results for obese patients 19 . However, previous evidence on influence of BMI on 1-year mortality is contradicting as other studies showed similar 1-year survival of obese patients compared to normal BMI patients 13 , 20 , 21 .…”
Section: Discussionsupporting
confidence: 75%
“…11,14,15,17,18 This is consistent with previously published studies. 29 Two biomarkers found to have a major influence on graft failure were pre-transplant creatinine and bilirubin. 12,14,15,17,18 Previous studies have highlighted this relationship as creatinine and bilirubin are useful indicators to assess overall kidney and liver health, both of which are crucial in cardiovascular health in the post-transplant patient.…”
Section: Other Major Factorsmentioning
confidence: 99%
“…Orthotopic heart transplant (OHT) is considered the reference standard treatment for patients with end-stage heart failure. With the obesity epidemic, there has been a consistent increase in body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) among transplant recipients over the last few decades . Patients with obesity on the transplant list face longer wait times, with each increase in BMI associated with a 4% lower likelihood of receiving a transplant .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with obesity on the transplant list face longer wait times, with each increase in BMI associated with a 4% lower likelihood of receiving a transplant . Similarly, the BMIs of the available donors have also increased by 1 BMI point from 2006 to 2020 …”
Section: Introductionmentioning
confidence: 99%